Association of socioeconomic status and overactive bladder in US adults: a cross-sectional analysis of nationally representative data - Lin, Weilong; Li, Taibiao; Xu, Zhengyuan; Chen, Peixin; Zheng, Qianqi; Hong, Ying-kai; Liu, Wei-juan (Frontiers in Public Health, 2024)
Socioeconomic status inequality is an important variable in the emergence of u rological diseases in humans. This study set out to investigate the association b etween the prevalence of overactive bladder (OAB) and the poverty income ratio (PIR) that served as a more influential indicator of socioeconomic status compared to education and occupation .Data from the National Health and Nutrition Examination Survey (NHANES) conducted from 2007 to 2020 were used in this cross-sectional study. The association between the PIR and OAB was examined using weighted multivariate logistic regression and weighted restricted cubic splines (RCS).Additionally, interaction analysis was used for investigation to the connections between PIR and OAB in various covariate groups in order to confirm the stability of the results.We observed a noteworthy inverse association between PIR and OAB after adjusting for potential confounding variables (OR = 0.87, 95% CI, 0.84 -0.90, P < 0.0001).PIR was transformed into categorical variables, and the association held steady after 2 that (1.0 < PIR <4.0 vs PIR ≤ 1.0, OR = 0.70, 95% CI =0.63 -0.77, P < 0.0001; PIR ≥ 4.0 vs PIR ≤ 1.0, OR = 0.56, 95% CI =0.48 -0.65, P < 0.0001).Additionally, RCS analysis showed that PIR and OAB had a negative nonlinear response relationship. Subgroup analyses showed that the inverse association between PIR and prevalence of OAB was stronger in obese than in nonobese individuals (P for interaction < 0.05).In our study, we observed a significant negative association between the PIR and the prevalence of OAB. In the future, PIR could be used as a reference standard to develop strategies to prevent and treat OAB.